Euro Area Policies : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Member Countries. (IMF Staff Country Reports; Country Report ;, 2019)
After a sharp slowdown starting in 2018, euro area growth is expected to recover over the course of 2019. However, mounting downside risks from global trade tensions, a no-deal Brexit, and market concerns about countries with high public debt emphasize the precarious nature of the forecast. Even in the absence of a major shock, there is a danger that the area could enter a prolonged period of anemic growth and inflation. Policies should focus on supporting growth while also reducing vulnerabilities.